Effective microbial disinfection in food industry with hydroxyl radical fumigation - Sangadkit, W.; Kongtrub, J. (My University, 2020)
Hydrogen peroxide (H2O2) fumigation has recently been explored and tested to be a good fumigant replacement of formaldehyde. This technique has been proven safer, less irritating and requires shorter exposure times. Surface disinfection has long been implemented with toxic formaldehyde or 35% hydrogen peroxide (H2O2). The results showed that they could be replaced with a safer and stronger oxidizing agent, activated H2O2 in a vaporized form. Aerosolization by aerosol generators has been used to produce aerosols containing hydroxyl radicals of hydrogen peroxide. The dispersal of this highly oxidizing mist of micron-size droplets destroyed Escherichia coli and Aspergillus niger colonies that have been artificially spiked on surfaces. The experiments demonstrated efficient disinfection by integrating 1 to 5% H2O2 fumigation with ozone (O3) and ultraviolet light (UV-C). Studies with E. coli and A. niger showed some disinfection with either O3 or UV-C. Combining H2O2 fumigation with both O3 and UV-C exposure considerably accelerated the microbial inactivation. This approach allowed fast disinfection with 1 to 5% H2O2 while offering cheaper and safer disinfection for healthcare settings.
Keywords: Fumigation; Hydrogen peroxide; Ozone; Surface disinfection; Ultraviolet